GRI 307 DAN MITIGASI KRISIS: ANALISIS KOMPARATIF KEPATUHAN LINGKUNGAN PERUSAHAAN DI TENGAH TREN BENCANA ALAM SUMATERA - Amelia Nurlita; Syarifatul Hayati; Andini Ramadhani; Zul Azmi (CV. Denasya Smart Publisher, 2026)
The escalation of hydrometeorological disasters in Sumatra has reached an alarming level, where ecosystem degradation is often exacerbated by failures in corporate environmental governance. This study aims to conduct a comparative analysis of corporate environmental compliance in Sumatra using the GRI 307 standard and to evaluate how reporting transparency correlates with the effectiveness of disaster mitigation and national regulations (Law No. 32/2009 on Environmental Protection and Management). The method employed is a descriptive-qualitative approach through content analysis of sustainability reports from the extractive and agricultural sectors. The results indicate a strong spatial correlation between low compliance levels (Red/Black PROPER ratings) and the occurrence of landslides and floods resulting from technical failures in slope stability and drainage systems. Conversely, companies that are transparent in reporting environmental sanctions tend to be more responsive in implementing technical improvements that function as early warning systems. This research demonstrates that GRI 307 transparency is a crucial predictive instrument for disaster mitigation. Suggested policy implications include the necessity of integrating the Ministry of Environment and Forestry (KLHK) sanctions database into the Financial Services Authority (OJK) reporting system to ensure the validity of green investments and the accuracy of disaster risk management in Sumatra.